A dress for the wicked - Krause, Autumn (HarperTeen, 2020)
For eighteen years in the sleepy town of Shy in Avon-upon-Kynt, Emmaline Watkins has feared her future would be just as sleepy and boring as her town. Then, in the glamorous capital city, Madame Jolène, head of the most prestigious fashion house in the country, opens her doors to take in girls from outside the city who want to get into the fashion business. Emmy thinks her dreams may yet come true--but, being the "first country girl" to compete in the fashion world will bring with it fierce prejudice and competition--and one girl seems intent on sabotaging her.